Manufacturing flow batteries using advanced 3D printing technology—A review - Wu, Ji; Xu, Shaowen (Frontiers in Chemical Engineering, 2023)
In the past decade, electrochemical energy storage (EES) systems such as rechargeable batteries have been explored as potential candidates to store intermittent power sources on a large scale. Redox flow batteries (RFBs) stand out by their low fabrication cost, high scalability, and long cycle life. A few pilot plants of RFBs with MWh capacity have been constructed worldwide, although their commercial profitability is still under investigation. 3D printing as a burgeoning technology offers unlimited opportunities in the process of optimizing the design, performance, and fabrication cost of RFBs as compared to traditional top-down manufacturing techniques. This review paper discusses the principles of various RFBs and 3-D printing techniques, followed by explaining the advantages, disadvantages, and major factors to consider when using 3-D printing for efficient redox flow batteries. Also, the practical applications of 3-D printing for RFBs with different redox chemistries in the past decade have been critically summarized, including classical all vanadium, Zn/Br, and novel new competitors as well. Lastly, a brief summary is provided along with several inspiring outlooks that may provide valuable guidance for the scientists who are interested in this research frontier.